The Effect of Compensation and Organizational Commitment on Work Satisfaction in Transportation Company - Yayuk Suprihatini; Indra Rustiawan; Muhamad Irpan Nurhab; Taryana Taryana; Arjang (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study is to ascertain how organizational commitment and pay affect employee job satisfaction. The dissemination of questionnaires and the usage of library data were the approaches used in this study's quantitative methodology. Using the saturated sample method, 50 employees made up the study's sample. Using SPSS 22 for data analysis, multiple linear regression is the method employed. The data quality test, the conventional assumption test, the hypothesis test, and the coefficient of determination are the data analysis techniques that are employed (R2). The findings of this study suggest that organizational commitment and salary have a considerable impact on employee job satisfaction, either partially or simultaneously. Employee work satisfaction is most strongly influenced by organizational commitment.